Problems of E-Learning During the Covid-19 Pandemic - Achmad Wildan Suyuti; Giyoto Giyoto; Imam Makruf (Ridwan Institute, 2022)
The learning process in educational institutions during the Covid-19 pandemic has several problems faced. The Ministry of Education and Culture took a firm stance through several circulars related to education policies in the emergency period of the spread of Covid-19. This paper examines the implementation of education policies during the Covid-19 pandemic related to distance learning policies. The distance learning process is a solution which in its implementation has not been optimal as a whole. There are things that must be considered in this distance learning, among others, the quality of teacher resources must be improved, both in terms of content and methodology as well as in terms of the use of information technology. In addition, students are also less active in participating in distance learning, either due to an unstable internet network or in terms of providing limited internet quota. The purpose of writing this article is to learn and understand the problems in learning activities during the pandemic, namely distance learning so that students can follow it actively and interestingly. This study uses a qualitative and observational approach. The results of this study prove that e-learning during the COVID-19 pandemic has caused various responses and changes to system that can affect the learning process and the level of development of students in responding to the material presented.